An Assessment of Sustainable Energy Management at a Major United Kingdom Based Hub Airport: A Case Study of London Gatwick Airport - Baxter, Glenn (International Journal of Environment, Agriculture and Biotechnology, 2023)
Due to their extremely energy intense nature, airports are increasingly focusing on their energy consumption and energy efficiency as a key part of their sustainability policies and strategies. Based on an in-depth longitudinal case study research design, this study has examined London Gatwick Airport, a major United Kingdom-based hub airport, sustainable energy management. The case study covered the period 2014 to 2021. London Gatwick Airport has two principal energy sources: electricity and natural gas. The case study revealed that London Gatwick Airport contributes to a lower carbon grid through its procurement of 100% certified renewable electricity. The airport has purchased this 100% certified renewable electricity since 2013. This measure has enabled the airport to mitigate its environmental impact. An important energy-related development at London Gatwick Airport, has been the airport’s waste processing and biomass generation facility, which began operations in November 2016. Category 1 and other types of organic waste are converted into biomass fuel that is used to power the processing plant and provide heating for the airport’s North Termina and the airport’s waste management site. The waste plant also provides power to the site’s water recovery system. Throughout the study period, London Gatwick Airport introduced a range of energy efficiency related measures. These measures include the installation of high efficiency lighting, heating, air conditioning, and ventilation (HVAC) systems, the upgrading of the airport’s boiler plant, the installation of an electricity powered hydrant dispenser, and the installation of more energy efficient light emitting diode (LED) lighting. The airport is also replacing its fleet of airport vehicles with electric powered vehicles. In addition, the airport is transitioning towards the use of electricity powered ground service equipment (GSE).